Dynamic stability improvement of grid connected converter using fuzzy compensator control - Rosyadi, M.; Takahashi, R.; Tamura, J.; Muyeen, S.M. (2012)
In this paper fuzzy compensator controller is proposed in order to improve dynamic stability of grid connected converter through LC filter. The fuzzy logic technique is used to regulate the parameters of PI controller by injected gain compensator according to deviation of grid voltage. Linear block model of the grid connected converter system is also developed to obtain dynamic response fast and easily for stability analysis. To evaluate the capability of the control system, 5 MW class of the converter is considered in this study. The simulation studies have been performed using Matlab/Simulink. It is concluded that the proposed control system can improve the dynamic stability effectively.